Berry tannin structure and phenolics evolution in cv. Cabernet Sauvignon (Vitis vinifera L.) : effect of light and temperature - Blancquaert, Erna (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.